Impelementasi Perda Pemberantasan Pelacuran di Kabupaten Lamongan - Slamet Sugianto (Fakultas Syariah dan Hukum UIN Sunan Ampel Surabaya, 2019)
Prostitution evolves along with the progress of civilization, although the fact that prostitution has certainly harmed people's lives. In legal terms, the problem of prostitution in Indonesia has not been fully regulated in the Criminal Code. To fill this legal vacuum, the local government of Lamongan regency issued regulation number 10 of 2004 which essentially regulates the prohibition of prostitution, adultery, or indecent acts. The article is the result of field research in Lamongan District on the Implementation of Perda No. 10 of 2004 concerning the Eradication of Prostitution in Lamongan District. At the end of this article, the conclusion is that the implementation of regulation No. 10 of 2004 concerning the prohibition of prostitution turned out to be less effective. Also, the media of resolving prostitution conflict can be completed through the court whereas the sanctions can be given in the form of a one-month prison sentence. Besides, the enforcement can also be done directly by Satpol PP (PPNS investigators) who work together with social services by assisting prostitutes affected by arrests.